Think about the new normality post COVID 19 with new ways and styles of life - Lian Roque Roque; Blanca Rosa Garcés Garcés; Itala del Rosario Díaz Suárez (Medisur, 2020)
Undoubtedly, COVID 19 has been a threat to human well-being. In this situation, a change is imposed in the ways and styles of life, even in the phase of the so-called new normality. The purpose of this work is to reflect, based on the approach of social studies, on the influence of modes, styles of action and life, for a better social confrontation in the named stage of facing the disease. The analysis carried out allows us to affirm that the adoption of new codes and lifestyles in the transition towards the new normality, based on the individual responsibility of each citizen, will generate a change in the physical and mental health of each individual in particular and of the population. in general, hence they are concepts whose theoretical approach is necessary. They are also very present constructs in the media, scientific debates and in everyday life, therefore reflection on these is extremely important.